VOLCANICS AND RUBY SUMIAKATRA, ISLAND MADAGASCAR - Troshenko, V.; Bublyk, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Indeterminate aged volcanics analysis, which are in the central part of Madagascar island has shown the conformity to tholeiite and similarity to the late cretaceous basalts of Madagascar island. Xenogenetic volcanic components indicate the prevalence of precious corundum to the bottom, ultra mafites of crust parts. Precious corundums locations lithologic control salite rocks in case of sapphires; mafites and ultramafites in case of rubine are given.